Influence of exercise order in a resistance-training exercise session - Spreuwenberg, L. P. B.; Kraemer, W. J.; Spiering, B. A.; Volek, J. S.; Hatfield, D. L.; Silvestre, R.; Vingren, J. L.; Fragala, M. S.; Häkkinen, K.; Newton, R. U.; Maresh, C. M.; Fleck, S. J. (The Journal of Strength and Conditioning Research, 2006)
The order of resistance exercises within a training session may have a vital impact on the quality of the constituent exercises performed. However, very few studies have documented the specific influence of exercise order. Therefore, the purpose of this study was to examine the effect of exercise order on back squat performance in the context of a whole-body workout. Nine resistance-trained male subjects (age: 24 ± 4 years, body mass: 81.5 ± 15.3 kg, resistance-training experience: 7 ± 4 years) performed the back squat exercise (4 sets at 85% of 1 repetition maximum) on 2 separate occasions in a balanced, crossover design. During one protocol, the squat exercise was performed first (protocol A); during the other protocol, it was performed after a whole-body resistance-exercise session (protocol B). Number of repetitions, average power, and rating of perceived exertion (RPE) were collected during each set of the squat exercise. All subjects performed significantly (p < 0.01) more repetitions during set 1 when they performed protocol A (8.0 ± 1.9 repetitions) compared with protocol B (5.4 ± 2.7 repetitions). The average power for each set was higher during protocol B compared with protocol A. There were no significant differences in RPE values between the 2 protocols. In conclusion, performing the barbell back squat first in an exercise session allowed the completion of more total repetitions. However, this study showed that performing the squat exercise after a whole-body workout session may result in greater power output if the squat is preceded by a power exercise (i.e., hang pull). This phenomenon may have been due to postactivation potentiation.